Oxidative Stress Mediated Therapy in Patients with Rheumatoid Arthritis: A Systematic Review and Meta-Analysis - Katarina Djordjevic; Andjela Milojevic Samanovic; Mirjana Veselinovic; Vladimir Zivkovic; Victor Mikhaylovsky; Maria Mikerova; Vladimir Reshetnikov; Vladimir Jakovljevic; Tamara Nikolic Turnic (MDPI AG, 2023)
Objective: The aim of this meta-analysis is to explore all the available literature to obtain updated data about the potential use of antioxidants in the treatment of rheumatoid arthritis (RA) and its ability to reduce disease progression and cardiovascular risk. Methods: This systematic review and meta-analysis was performed strictly in accordance with the PRISMA guidelines. English and Chinese databases were searched with a retrieval time up to March 2023. These databases included the PubMed, Embase, Medline Complete, Web of Sciences and Cochrane Collaboration, Wanfang, China National Knowledge Infrastructure, and VIP databases. This literature search was formulated by the two researchers independently. The search strategy consists of reading, collecting the literature, and conducting the preliminary screening. After that, they provide the final selection of the literature according to the inclusion criteria and data extraction. Also, for all studies, the risk bias was assessed to evaluate the quality of the included references. The content of the risk assessment of bias included the following criteria: random allocation method, allocation plan hiding, blind method, completeness of result data, and selectivity of reporting of results, as well as other biases. The main outcomes were clinical efficiency of antioxidant therapy (C-reactive protein, DAS28 score, HAQ, Number of tender joints, etc.) and oxidative stress indicators (catalase, superoxide dismutase, or total antioxidant capacity). Results: We observed, in most of the studies, the small or moderate effects of antioxidant treatment. The mean effect size is 0.525, and that means that moderate effects were observed in 30 selected RCTs. Also, this effect is confirmed in the 1652 patients with RA with the mean confidence interval of 0.276 (lower limit) and 0.983 (upper limit). Cohen coefficient was calculated at 0.05. Conclusion: The existing evidence is that antioxidants can reduce systemic and local oxidative stress and can reduce damage as the main agent involved in autoimmune diseases such as rheumatoid arthritis.